Kepemimpinan Rohani dan Akuntabilitas Moral: Sebuah Respons Teologis-Biblika terhadap Fenomena Korupsi di Indonesia - Setio Dharma Kusuma; Onesiporus Pengharapan Lase (Unit Penerbitan Informasi dan Teknologi Sekolah Tinggi Teologi Gereja Kalimantan Evangelis (STT GKE), 2026)
The corruption crisis that afflicts Indonesian society is not merely a legal or governmental issue, but also reflects a profound spiritual crisis. This article examines the integration between spiritual leadership and moral accountability as a biblical response to the phenomenon of corruption. Employing a qualitative approach through theological literature study, the research interprets 1 Samuel 2:12–36 to trace the roots of leadership failure in the sons of Eli as an example of moral deviation and the loss of spiritual responsibility. The findings indicate that corruption arises from the disintegration between faith and morality, as well as the misuse of authority that ought to be oriented toward service. This study reveals that genuine spiritual leadership, rooted in the fear of the Lord and biblical integrity, stands as the antithesis of corrupt practices. The implications highlight the central role of the church and Christian educational institutions in shaping accountable leadership through character formation and transformative spirituality.